(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Steroid hormone receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on Nuclear Hormone Receptors [65, 193]) are nuclear hormone receptors of the NR3 class, with endogenous agonists that may be divided into 3-hydroxysteroids (estrone and 17β-estradiol) and 3-ketosteroids (dihydrotestosterone [DHT], aldosterone, cortisol, corticosterone, progesterone and testosterone).